The aesthetics of disillusionment: teachers' narratives of "disillusioned transformation" - Chiu, Yin Yung; Fleming, Ted (Behavioral Sciences, 2025)
This article explores the emotional transformations of teachers since the pandemic, shifting from idealised passion for their profession to a more balanced, self-preserving approach to their work and mental well-being. Through four case studies of teachers from Hong Kong, Australia, and France, this paper examines how teachers navigate emotional wisdom in response to trauma and burnout and how such wisdom informs their ability to recognise when to prioritise their mental health over job prospects. The idea of disillusioned transformation will be explored: when teachers who are initially invested in a set of ideals in their roles become disillusioned and disengaged but through which find emotional balance and the resilience towards new sources of professional fulfilment. Central to transformative learning theory, this study highlights how trauma (moral injury, systemic trauma) and emotional wisdom contribute to teachers’ critical reflection and self-preservation. This article seeks to delineate the intersection between emotional wisdom, aesthetic emotions, and trauma recovery and to understand how teachers transform their professional identity in response to emotional distress, fostering a more sustainable and healthy approach to teaching.
Gesehen am 26.11.2025